Critical Thinking in Islamic Educational Tradition and Its Relevance to 21st Century Skills - Ramadhan, Habibie; Arsyad, Junaidi (Journal of Educational Sciences, 2025)
Islamic education has a long-standing tradition of integrating intellectual and moral development, rooted in the Qur’an and Sunnah, to form balanced individuals. In the modern era, the need to align these traditions with the demands of 21st-century education becomes increasingly urgent. This study aims to analyze the development of critical thinking in Islamic educational traditions and its relevance to 21st-century skills. The research method used is a qualitative narrative approach through library research, examining written sources such as books, journals, and articles to understand concepts and phenomena in depth. The results of the study indicate that since its inception, Islamic education has emphasized the use of reason and reasoning in the learning process through the practices of ijtihad, deliberation, and scientific tolerance. This tradition forms the foundation of critical thinking relevant to modern learning. The integration of Islamic values with 21st-century skills, particularly the 4C skills (critical thinking, creativity, communication, and collaboration), has the potential to improve the quality of Islamic education and prepare students to face global challenges intelligently, adaptively, and with character. This research provides a conceptual contribution to the development of curricula and learning strategies that combine Islamic knowledge with the demands of 21st-century skills.